Tactile Torso Display For Fighter Pilots – Wing-Oriented And Horizon-Oriented Presentation. (September 2013) - Svensson, Jonathan; Andersson, Peter; Alfredson, Jens; Holmberg, Johan
The demonstration proposed will feature two different tactile presentation principles in a software flight simulation which presents missile warnings multimodally using a tactile torso display, audio, and a visual display. In a recent experiment, the tactile torso display with 36 tactors in three rows by 12 columns was developed and integrated into a fighter flight simulator. Two principles of tactile presentation for warnings of incoming missiles were used and compared to using no tactile display when performing evasive maneuvers. The tactile presentation of the vector to the missile was either oriented to the horizon or to the aircraft's wings, taking pitch and roll into account. Results indicate no significant difference in reaction time or maneuver completion time between principles; however pilots were positive to the tactile display and could see benefits of both presentation principles in different situations.